Population Prevalence of Premature Truncating Variants in Plakophilin-2 and Association With Arrhythmogenic Right Ventricular Cardiomyopathy: A UK Biobank Analysis. (10th May 2022) - Hylind, Robyn J.; Pereira, Alexandre C.; Quiat, Daniel; Chandler, Stephanie F.; Roston, Thomas M.; Pu, William T.; Bezzerides, Vassilios J.; Seidman, Jonathan G.; Seidman, Christine E.; Abrams, Dominic J.
Abstract : Background: Truncating variants in the desmosomal gene PKP2 (PKP2 tv) cause arrhythmogenic right ventricular cardiomyopathy (ARVC) yet display varied penetrance and expressivity. Methods: We identified individuals with PKP2 tv from the UK Biobank (UKB) and determined the prevalence of an ARVC phenotype and other cardiovascular traits based on clinical and procedural data. The PKP2 tv minor allelic frequency in the UKB was compared with a second cohort of probands with a clinical diagnosis of ARVC (ARVC cohort), with a figure of 1:5000 assumed for disease prevalence. In silico predictors of variant pathogenicity (combined annotation-dependent depletion and Splice AI [Illumina, Inc.]) were assessed. Results: PKP2 tv were identified in 193/200 643 (0.10%) UKB participants, with 47 unique PKP2 tv. Features consistent with ARVC were present in 3 (1.6%), leaving 190 with PKP2 tv without manifest disease (UKB cohort; minor allelic frequency 4.73×10 −4 ). The ARVC cohort included 487 ARVC probands with 144 distinct PKP2 tv, with 25 PKP2 tv common to both cohorts. The odds ratio for ARVC for the 25 common PKP2 tv was 0.047 (95% CI, 0.001–0.268; P= 2.43×10 −6 ), and only favored ARVC (odds ratio >1) for a single variant, p.Arg79*. In silico variant analysis did not differentiate PKP2 tv between the 2 cohorts. Atrial fibrillation was over-represented in the UKB cohort in those with PKP2 tv (7.9% versus 4.3%; odds ratio, 2.11; P =0.005). Conclusions: PKP2 tv are prevalent in the population and associated with ARVC in only a small minority, necessitating a more detailed understanding of how PKP2 tv cause ARVC in combination with associated genetic and environmental risk factors.